(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article provides information about the need to effectively use interactive methods in order to develop communicative competence in the teaching of foreign languages. It is also devoted to the issues of forming the debate method among university students and improving their oral speech competence.